1969
DOI: 10.1111/j.1464-410x.1969.tb11881.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Sinus Lipomatosis: A Report of Twenty-Six Cases

Abstract: SUMMARY A review of 3,500 intravenous pyelograms of patients attending a general hospital has been carried out and has shown an incidence of 0.66 per cent, for radiologically diagnosed renal sinus lipomatosis. Material obtained from this review and previously published literature suggests that there is no significant sex preponderance, that the entity is most commonly discovered in the sixth decade of life, and that possible aetiological factors are urinary stones, chronic pyelonephritis, obesity and hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The first case was described in 1841 by Rayer [ 10 ] occurring in an autopsy performed in 1837 [ 11 ]. Several reported cases have been reported in the English literature, the majority of which are individual case reports and a few large case series [ 2 , 3 , 12 ]. Renal replacement lipomatosis is a rare, benign condition characterized by prominent fat proliferation of the renal sinus with atrophy of the renal parenchyma that may mimic other renal malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The first case was described in 1841 by Rayer [ 10 ] occurring in an autopsy performed in 1837 [ 11 ]. Several reported cases have been reported in the English literature, the majority of which are individual case reports and a few large case series [ 2 , 3 , 12 ]. Renal replacement lipomatosis is a rare, benign condition characterized by prominent fat proliferation of the renal sinus with atrophy of the renal parenchyma that may mimic other renal malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…A pericardial accumulation of fat tissue is present (arrow 3). course, such as multiple symmetric lipomatosis (Enzi, 1984), pelvic lipomatosis (Engels, 1959), renal sinus lipomatosis (Windholz, 1957;Poilly et al, 1969), mediastino-abdominal lipomatosis , lipomatosis dolorosa (Dercum, 1942). …”
Section: Discussionmentioning
confidence: 99%
“…It is a rare complication and mostly described literature is for unilateral disease. According to one research, the incidence of RRL was found to be 0.66% in 3,500 cases of intravenous pyelogram and the ailment has no sex preponderance [ 2 ]. In the past, histopathological examination was pivotal for the diagnosis, but immense use of imaging studies has improved our knowledge to diagnose the disease in a non-invasive manner.…”
Section: Introductionmentioning
confidence: 99%